ANALISIS PENGARUH BIAYA PROMOSI, BIAYA PENGEMBANGAN PRODUKSI, BIAYA SALURAN DISTRIBUSI TERHADAP PENJUALAN PADA PT POLIPLAS MAKMUR SANTOSA UNGARAN - Rochmah, Siti (JURNAL STIE SEMARANG, 2016)
The purpose of this study is to analysis influence promotion costs, costs of production and cost of distribution channel to sales at PT. Poliplas Makmur Santosa Ungaran. both parsial sampel in this case is used as a sample company data relating to the cost of the promotion, distribution channel costs, and the cost of production and sales of PT. Poliplas Makmur Santosa per month for a period of 3 years ie from 2013 to 2015. Data collection methods Analysis tool used is the classical assumption test, multiple linear regeresi using t test. From the results of this study are: the influence of sales promotion costs are significant, it is proved by the results of t = 4,752> t table 2.037 and 0.000 disignifikan <sidnifikan a = 0.05. Thus hipotes stating the suspect is no effect of the cost of production (X2) to sales (Y) is proved. Influence of cost distribution channel to sales is significant, it is proved by the results of t = 3.344> t table 2.037 and 0.002 significance <significance a = 0.05. Thus the hypothesis that there is suspected effect of the cost of distribution channels (X3) to sales (Y) is proved